HUMAN RESOURCES STIFIn AS A HUMAN RESOURCES MANAGEMENT INNOVATION: ITS IMPACT ON EMPLOYEE PERFORMANCE IN ISLAMIC SCHOOLS - Karasna, Danang; Diandra, Didip; Haikal, Fahri; Priyono, Agung (Journal of Management and Leadership, 2025)
This study explores the application of the Human Resources (HR) STIFIn method as an innovative approach to human resource management in Islamic educational institutions, focusing on its impact on employee performance. STIFIn is a personality profiling method based on genetic intelligence, identifying five dominant "Machines of Intelligence": Sensing, Thinking, Intuiting, Feeling, and Instinct. Conducted at Aya Sophia Islamic School, this qualitative research adopts a case study approach to analyze how HR STIFIn is implemented in organizational practice, and how it influences work productivity, communication, and collaboration among teachers and staff. Findings show that HR STIFIn improves task suitability, enhances motivation, and supports harmonious working relationships by aligning responsibilities with individual cognitive tendencies. The study also identifies critical supporting factors, including strong leadership commitment and internal STIFIn expertise, At the same time, challenges include the need for continuous training, among new staff, and integration with parents' understanding. The research concludes that HR STIFIn not only boosts employee performance but also fosters a personalized and humanistic work culture. This model offers a promising alternative for Islamic schools aiming to integrate character-based education with strategic HR development.